1993
DOI: 10.1111/j.1525-1594.1993.tb00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience and Model Analysis on Beta‐2‐Microglobulin Kinetics in High‐Flux Hemodialysis

Abstract: Beta-2-microglobulin (P2M) is associated with amyloidosis. The study of P2M kinetics can provide information on the elimination of this uremic toxin. A P2M kinetic model modified from Gotch, considering the volume changes between intracellular, interstitial, and intravascular compartments and the generation stimulation and inhibition during hemodialysis is proposed. The clinical experiments on 8 stable hemodialysis patients treated with polysulfone (F80) and polymethyl methacrylate (PMMA, BK2.lp) 3 times a wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…To support what we believe to be a somewhat commercially biased premise, Dr Labib has only selected data associated with a cellulose triacetate membrane, now being utilized in a fraction of all procedures, and has chosen to ignore the vast majority of the HEMO study data that demonstrated that the beta-2 microglobulin removal rate of F80 polysulfone dialyzers remained quite stable, with only an 11% decrease in removal rate over 10 uses 2 . The HEMO study correlates well with the work of Lain et al 3 that cites instances of an 18% decrease in beta-2 microglobulin clearance over a single treatment.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…To support what we believe to be a somewhat commercially biased premise, Dr Labib has only selected data associated with a cellulose triacetate membrane, now being utilized in a fraction of all procedures, and has chosen to ignore the vast majority of the HEMO study data that demonstrated that the beta-2 microglobulin removal rate of F80 polysulfone dialyzers remained quite stable, with only an 11% decrease in removal rate over 10 uses 2 . The HEMO study correlates well with the work of Lain et al 3 that cites instances of an 18% decrease in beta-2 microglobulin clearance over a single treatment.…”
supporting
confidence: 85%
“…It was not our intention to provide a comprehensive evaluation of that literature -there are several excellent reviews of this subject in the literature, including two recent publications by Twardowski. 3,4 The studies that we cited in our manuscript included data on multiple dialyzers (and not just the cellulose triacetate membranes, as stated by Mr Carlson). For example, the study by Leypoldt et al 5 reported a significant reduction in b 2 -microglobulin clearance for polysulfone dialyzers reprocessed with peracetic acid, with very similar results reported by Ouseph et al The permeability data reported in our study are also consistent with the results of Wolff and Zydney 8 from prior in vitro studies using peracetic acid reprocessing.…”
Section: Response To 'Comments On Water Permeability Of High-flux Dialyzer Membranes'mentioning
confidence: 99%
“…Previous investigators have assumed that b 2 -microglobulin is generated in only one compartment. 2,[18][19][20][21][22] However, b 2 -microglobulin is expressed on the surface of most nucleated cells making it more likely that free b 2 -microglobulin is generated in both compartments. Most prior investigations 2,18,22 have assumed that mass transfer of b 2 -microglobulin between the two compartments occurs by diffusion, only.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, many prior studies of b 2 -microglobulin kinetics have assumed that the distribution volume for b 2 -microglobulin corresponds to extracellular fluid and they have also assumed that volume to be equal to one-third of the total body water. 18,[20][21][22] We allowed the volume of distribution to vary and obtained an estimate based on the best fit of the model equations to the experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the types of solute examined in this study may not have been sufficient to verify the difference in clearance between the two membranes. For example, we did not consider solutes such as β2 microglobulin or inflammatory cytokines, which have been well validated in recent years [24][25][26]. However, we examined the difference in the clearance of HMGB-1, which has been the focus of attention in recent years, and reported a difference between the two polysulfone membranes in its clearance.…”
Section: Discussionmentioning
confidence: 99%